ADP-Induced Platelet Adhesiveness as a Diagnostic Test in von Willebrand’s Disease) - Ödegaard, A. E; Skâlhegg, B. A; Hellem, A. J (Thrombosis and Haemostasis, 1964)
In von Willebrand’s disease the ADP-induced platelet adhesiveness in plasma is zero at a final concentration of 0.05 µg/ml. Several coagulopathies react as normals giving a detectable platelet adhesiveness ranging from 18% to 44%. This may be used as a diagnostic test in von Willebrand’s disease.